Milk Production Coefficient Of Monbelyard Cows By Production Direction - Ulugbek Erkulov; Utkir Rajabovich Soatov; Oxun Razzaqovich Kuchchiev; Bobir Bahodirovich Shayusupov; Guzal Mirulug’ovnaErdanova (Zien Journals, 2022)
In this article, selection works are carried out taking into account the types of body structure of Montbelyard cattle, characteristics of milk product production per 100 kg of live weight, as well as higher milk yield of Montbelyard cows with milk body structure compared to milk-meat and meat-milk cows. information is provided.
Keywords: Montbelyard breed; cow; milk; body structure